(untitled) (Research, Society and Development, 2021)
Aim: To identify the relationship between COVID-19 and acute kidney injury, as well as the role of the multiprofessional approach in this scenario. Methodology: This is a narrative review carried out from the PubMed, SciELO and LILACS databases, using the descriptors "COVID-19" and "Acute Kidney Injury". The inclusion criteria were: original published studies available in full for reading, published in the last 5 years, in Portuguese, English and / or Spanish. Veterinary articles were excluded, as well as those that evaluated patients with chronic kidney diseases previous to infection by COVID-19 or transplanted patients, isolated abstracts and editorial letters. Results: SARS-CoV-2 uses angiotensin 2-converting enzyme and type 2 transmembrane serine proteases to invade human cells, causing a systemic inflammatory response because of cytokine storm; direct cytotropic effect induced by virus; and acute tubular necrosis, due to multiple organ failure and shock. Rhabdomyolysis contributes to this condition. Clinically, patients with acute kidney injury and COVID-19 may present genitourinary symptoms, diarrhea, proteinuria, hematuria and changes in urea and creatinine. The approach to the nephrological patient in a pandemic context involves reinforcement of preventive measures against the new virus, effective health management and collaboration between doctors and nurses of different specialties, especially intensivists and nephrologists. Conclusion: SARS-CoV-2 infection can cause acute kidney injury due to direct viral toxicity or dysregulation of immunological mechanisms. The clinical picture in these cases is marked by symptoms of kidney failure and infection. The synergistic performance of the multiprofessional health team and health managers is essential in this scenario.